Saturday

April 19, 2014

April 19, 2014

Posted by **Chelsie** on Tuesday, October 11, 2011 at 10:23pm.

- Calculus -
**Reiny**, Tuesday, October 11, 2011 at 10:51pmf(x+h) = (x+h)^2 - 2(x+h) - 3

= x^2 + 2hx + h^2 - 2x - 2h - 3

**Related Questions**

Calculus AB - Find the indefinite Integral of: (e^(2x)-e^(-2x))/(e^(2x)+e^(-2x))...

COLLEGE CALCULUS. HELP! - the fundamental theorem of calculus, f(x)=∫(0,x...

Calculus - Find the normals to the curve xy + 2x - y = 0 that are parallel to ...

Calculus - Find the normals to the curve xy + 2x - y = 0 that are parallel to ...

Calculus - Find the equation of the tangent line to the curve y=1+ xe^(2x) y'=(e...

calculus - find the following derivatives: f(x) = (2x+5)/(x^2-3) f'(x)= (2)*(x^2...

pre-calculus - (tan^2x-9)(2cosx+1)=0 Find one period 4cos^2x-4cosx+1=0 find all ...

Calculus - Find the derivative of y=cot³(1-2x)² y'=3[cot(1-2x)²]² (-csc²(1-2x...

Calculus; Product Rule - Find the value of dy/dx for the given value of x. a) y...

Pre-calculus-check answers - If f(x)=4x^2 and g(x)=2/x, find [g x f](x). Answer...